Three-Dimensional Evaluation of the Changes at the Sagittal Split Osteotomy Line after Mandibular Setback Surgery - (:unkn) unknown (AVES PRESS LTD, 2016)
Objective: The aim of this study was to evaluate three-dimensional positional changes at the sagittal split osteotomy (SSO) line after double jaw surgery for class III patients and determine the effect of maxillary impaction at the SSO line. Methods: In this study, cone-beam computed tomography scans of 21 Class III patients taken before and 3-6 months after orthognathic surgery were used. Twenty-one patients were divided into two groups: Group I consisted of 10 patients who had combined maxillary advancement, maxillary impaction, and mandibular setback surgery, and Group II consisted of 11 patients who had combined maxillary advancement and mandibular setback surgery. Three-dimensional cone-beam computed tomography images were registered using cranial base superimposition and the changes of the SSO line were examined based on the three-dimensional reconstructed images. Results: Medial displacement of the SSO line was statistically significant on the axial plane in Group II (p<0.05). Comparison of the changes between Groups I and II showed that the amount of displacement of the SSO line in the axial plane in Group II was significantly greater than that in Group I (p<0.05). Conclusion: In cases that have maxillary advancement and mandibular setback surgery, significant medial displacement of the SSO line was observed. There was no significant change in patients who had combined maxillary advancement, impaction, and mandibular setback surgery.
Keywords: Sagittal split osteotomy; mandibular setback; cone-beam computed tomography